An Investigation of the Acoustic Enclosure of an Air Conditioning Compressor Using Response Surface Analysis and Topological Rigidity Optimization - Hai-Feng Cao; Cang-Jie Yang; Ren-Lian Ma; Shi-Wei Ni; Zheng-Kai Song; Xi Wang; Yu-Xuan Chen; Chen-Xing Jiang (Shock and Vibration)
A novel split-type air conditioning system is introduced to balance usability and portability. Unlike conventional split-type systems, where the compressor is typically placed outside, this system situates the compressor within the indoor unit, which may expose users to compressor noise. There are prominent peaks in the compressor noise spectrum, particularly at the compressor operating frequency and its harmonics, notably the second and third harmonics. The research presents a multilayered acoustic enclosure specifically designed for air conditioning compressors to address this issue without modifying the compressor or indoor unit casing. In order to get better sound insulation performance, a response surface methodology (RSM) is applied to optimize the thickness ratio, open area ratio, and open area height of the acoustic enclosure with predefined thickness. In addition, topological optimization is employed to strengthen weak areas of the acoustic enclosure. Then, experimental trials using the proposed acoustic enclosure are conducted in a semianechoic chamber. Results demonstrate significant reductions in noise levels, including 7.99 dB(A), 5.69 dB(A), and 5.19 dB(A) reductions in the fundamental frequency, second harmonic, and third harmonic noise of the compressor’s operating frequency, respectively.